Pengaruh Literasi Keuangan Syariah, Persepsi Kemudahan, Persepsi Kegunaan, Fitur Layanan dan Keamanan Terhadap Minat Menggunakan E-Money Linkaja Syariah (Studi Kasus pada Generasi Z di Kota Serang) - Mukhsin, Moh; Atiah, Isti Nuzulul; Bahtiar (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
This research aims to analyze the influence of sharia financial literacy, perceived convenience, perceived usefulness, service features and security on interest in using LinkAja Syariah e-money among generation Z in Serang City. This research uses a quantitative approach with associative methods. Primary data was collected through questionnaires distributed to 290 generation Z respondents using cluster sampling techniques. Partial test results show that sharia financial literacy, perceived convenience, perceived usefulness, and service features have a positive and significant effect on interest in using LinkAja Syariah e-money. However, the security variable has no significant effect. Simultaneous test results state that all variables together have a significant effect on interest in use. These findings reinforce the importance of sharia literacy and perceived ease of technology in encouraging the adoption of e-money based on sharia principles. Keyword: E-Money, Interest in Using, LinkAja Syariah, Perception of Convenience, Perception of Usefulness, Security, Service Features, Sharia Financial Literacy